Nanoporous silicon nitride-based membranes of controlled pore size, shape and areal density: Fabrication as well as electrophoretic and molecular filtering characterization - Seidenstücker, Axel; Beirle, Stefan; Enderle, Fabian; Ziemann, Paul; Marti, Othmar; Plettl, Alfred (Beilstein Journal of Nanotechnology, 2018)
A new route will be presented for an all-parallel fabrication of highly flexible, freestanding membranes with well-defined porosity. This fabrication is based on arrays of well-defined Au nanoparticles (NPs) exhibiting a high degree of hexagonal order as obtained in a first step by a proven micellar approach. These NP arrays serve as masks in a second reactive ion etching (RIE) step optimized for etching Si and some important Si compounds (silicon oxide, silicon nitride) on the nanoscale. Application to commercially available silicon nitride membranes of well-defined thickness, delivers a diaphragm with millions of nanopores of intended and controlled size, shape, and areal density with narrow distributions of these parameters. Electrophoretic transport measurements indicated a very low flow resistance of these porous membranes in ionic solutions as expected theoretically. Size-selective separation of protein molecules was demonstrated by real-time fluorescence microscopy.
Keywords: ion transport; micellar technique; molecular filtration; nanopores; solid-state membrane